The Norwegian CDI-III as an assessment tool for lexical and grammatical development in preschoolers - Holm, Elisabeth; Hansen, Pernille Bonnevie; Romøren, Anna Sara H.; Garmann, Nina Gram (Frontiers in Psychology, 2023)
Parental report instruments are a non-invasive way to assess children’s language development and have proved to give both valid and reliable results when used with children under the age of 2;6 (and in some cases up to 3). In this study we examine the newly developed Norwegian edition of a language assessment tool for older preschoolers: MacArthur-Bates Communicative Development Inventory III (CDI-III), investigating whether this parental report tool can be used for assessing the language of monolingual Norwegian-speaking children between 2;6 and 4 years. NCDI-III results for 100 children between 2;6 and 4.0 are presented. All sections were significantly intercorrelated. All sections except Pronunciation showed growth with age. Internal consistency was measured both in terms of Cronbach’s alpha and corrected item-scale correlation, and the results are discussed considering features of item difficulty distribution. Methodological considerations are discussed, as well as implications relevant both for possible later revisions and for CDI-III adaptations to new languages.